ANALISIS PENGARUH BANTUAN SOSIAL PKH TERHADAP KESEJAHTERAAN MASYARAKAT PKH DI KECAMATAN PANGGUNGREJO KABUPATEN BLITAR - Rohana Widhi Lestari; Abu Talkah (Universitas Islam Kadiri, 2020)
The purpose of this study is to determine the effect of the Family Hope Program on the social welfare of underprivileged communities in the District of Panggungrejo. The population of this study were residents of the District of Panggungrejo. While the sample in this study is Very Poor Households (RTSM) who received a Family Hope Program. Assistance from the Family of Hope Program and those directly related to the community in Kecamatan Panggungrejo totaling 55 samples. The analytical method used in this study is Multiple Regression Analysis. Based on the results of the study note that there is an influence of the Family Hope Program Against Community Welfare Panggungrejo District. In addition, one of the processes that determines the implementation of PKH in Panggungrejo District is the preparation of implementation steps in advance so that the desired objectives are achieved. The process of preparing for the Implementation of the Family Hope Program includes the preparatory process for implementation starting from the selection of districts / cities by BPS (Central Statistics Agency), determining the location of PKH recipients, selecting companions, and determining PKH participants. In addition, in the process of collecting data and information there must be cooperation between the relevant work units.